Assessing Forest Fires in The North Eastern Anatolia with Long Term Meteorological Parameters - Kadir Alperen Coşkuner (Doğal Afetler ve Çevre Dergisi)
This study examines the relationship between number of forest fires and burned areas, and meteorological parameters between 1987 and 2020 in the North Eastern Region of Turkey. A total of 1560 forest fires affecting 7340.7 ha forested lands within the border of Giresun, Trabzon and Artvin Regional Forest Directorate were analysed with historic mean annual temperature, relative humidity, wind speed, total annual rainfall and calculated Sweden Angstrom Index for a period of 1987-2020. Results indicated that total annual number of fires were positively correlated with mean annual temperature, and negatively correlated with mean annual relative humidity and total annual rainfall. No significant relationship was found between the total annual number of fires and the annual average wind speed. The lower Angstrom index values indicate high risk of fires and significant negative correlation was found between total annual number of fires and Angstrom index values. No significant relationship was found between the total annual burned area and annual average temperature, relative humidity, wind speed, and Angstrom Index values, however, a significant negative correlation was found with the total annual rainfall. The linear diminishing trend in the values of Angstrom Index and increasing trend in the number of fires from 1987 to 2020 in North Eastern Anatolia indicated that forest fires may become a major problem for forested lands in the North Eastern Region of Turkey in the future.